The effect of foreign language enjoyment on the willingness to communicate of non-English majors: the mediating role of L2 grit and academic buoyancy - Bai, Chun; Hu, Jiaying (Frontiers in Education, 2025)
IntroductionForeign language enjoyment (FLE) has emerged as a significant factor influencing learners’ willingness to communicate (WTC) given its critical role in shaping communicative behaviors in language learning. However, the relationship between second/foreign language (L2) grit, academic buoyancy, FLE and WTC remains under-explored. To address this research gap, this study surveyed 486 Chinese non-English majors studying English-as-a-foreign-language (EFL) to examine the effect of FLE on WTC, as well as the mediating effects of L2 grit and academic buoyancy.MethodsThe study primarily employs research methods such as descriptive analysis, Pearson correlation analysis, regression analysis and mediation effect analysis.ResultsThe research findings revealed medium levels of L2 grit and WTC, and high levels of FLE and academic buoyancy. The results of the Pearson correlation analysis revealed significant correlations between WTC and FLE, L2 grit and academic buoyancy (p < 0.01). Regression analysis confirmed that FLE and academic buoyancy were significant predictors of WTC, whereas L2 grit was not. Mediation analysis identified academic buoyancy as a mediator, establishing the pathway “FLE—Academic buoyancy—WTC” for the effect of FLE on WTC.DiscussionThese findings could provide practical guidance for cultivating and enhancing the WTC of non-English majors in L2 learning.